THE ROLE OF THE STATE AND MODIFICATIONS TO ISLAMIC FAMILY LAW IN MARRIAGE IN THE ISLAMIC WORLD - Mustafa Parinduri; Sukiati Sukiati; Iwan Iwan (AS-SAIS (JURNAL HUKUM TATA NEGARA/SIYASAH), 2026)
Marriage in Islamic family law is a fundamental institution that is not only governed by Sharia norms but has also evolved through state intervention in various Muslim countries. This study aims to analyze the role of the state in modifying Islamic family law, particularly regarding marriage, and to examine the forms and implications of these changes in the Islamic world. The method employed is a legal-normative approach with a comparative analysis of family law regulations in several Muslim countries. The results of the study indicate that the state plays a strategic role in codifying, unifying, and reforming Islamic family law to align with social and political demands and the changing times. These modifications include restrictions on polygamy, raising the minimum age for marriage, strengthening women’s rights, and regulating divorce procedures and marriage registration. Although based on Sharia principles, the implementation of Islamic family law in various countries demonstrates diversity influenced by local contexts and state policies. Thus, the state’s role in modifying Islamic family law is not merely administrative but also substantive in creating a legal system that is more responsive to social justice and the protection of human rights. This study confirms that the dynamics of Islamic family law are the result of the interaction between religious norms and state authority within the framework of modernity. Keyword: Islamic Family Law, Role of the State, Turkey, Malaysia, Indonesia, Legal Modifications.